2010
DOI: 10.1080/14650040903501104
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Mobility and the Financialisation of Development

Abstract: This article challenges popular claims about the capacity for microfinance to reduce poverty and empower women in the global South. Instead, I posit microfinance as a contradictory development tool, one that creates possibilities for both the contestation and continuation of unequal social relations at multiple scales. The article is divided into two major sections. I begin by examining the assumptions embedded in mainstream financial mappings of global space since the 1980s. In particular, I show how they pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 42 publications
0
32
0
1
Order By: Relevance
“…NOTES 1. Some exceptional studies that place microfinance in a global context and are attentive to the everyday institutional dimensions of making loans to women include: (Ly & Mason, 2012;Young, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NOTES 1. Some exceptional studies that place microfinance in a global context and are attentive to the everyday institutional dimensions of making loans to women include: (Ly & Mason, 2012;Young, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The interface between microfinance staff and their organizations has been understudied in the existing literature that focuses on staff in any capacity (Kar, 2013;Sagamba et al, 2013;Young, 2010). In the interface between PI and Kanchan's staff, I found that PI held their field staff to high targets and exacting requirements, and individual staff members navigate these pressures in relation to their own positions in class and organizational hierarchies and opportunities.…”
Section: Maya Addressing Kanchan Trainersmentioning
confidence: 90%
See 1 more Smart Citation
“…Roy ). Its competitive and calculative practices foster a market orientation among philanthropic grantees, many of whom are marginalized by race and gender as well as by poverty (Rankin ; Roy ; Young ). Through the process of winning grants and the rationale behind them, as well as through the funded projects themselves, recipients are encouraged to see the difference‐friendly freedoms and choices offered by the market as solutions to the forms of oppression in which they are mired; moreover, through the management of funds and “return on investment” mindset they are recruited to operate as agents who can become responsible for their own care (cf.…”
Section: The Triple Movement: Making Market Subjectsmentioning
confidence: 99%
“…Female heads of household are, not incidentally, also a “good risk”, providing the double benefit to funders of return on investment and the potential integration of previously marginalized economic subjects. This process relies on a newly delineated subject position Rankin () has termed, “rational economic woman” (see also Roy ; Young ); this rational woman must both learn from and manifest entrepreneurial ambitions and understandings, and be able and willing to take advantage of the opportunities offered to her.…”
Section: Out Of the Ruins: The Rise Of Millennial Philanthropymentioning
confidence: 99%